Numerical study of the behaviour of jointed tunnel lining - Barzegar, M.; Gharehdash, S.; Sharifzadeh, Mostafa (TMMOB Maden Muhendisleri Odasi, 2015)
This paper presents the results of a numerical study that has been performed to investigate the factors affecting the maximum bending moment induced in a jointed tunnel lining. The effects of joint number and orientation have been studied in detail. Observations of the results demonstrate that increasing joint number reduces the maximum bending moment induced in the lining. However, the effects of joint number and orientation on the maximum bending moment induced in the tunnel lining become insignificant once the critical joint number has been exceeded. In addition, the sensitivity of the joint number to various ground conditions, tunnel depths and lining flexibility are also highlighted. From the parametric studies, a simple design methodology is proposed to facilitate the determination of maximum bending moment induced in a jointed tunnel lining without incorporating joints in the analysis.